Gelatinous transformation of the bone marrow complicated by self induced starvation (Medical Journal of Indonesia, 2002)
Gelatinous bone marrow transformation (GMT) is rare. It has been found to be associated with severe illnesses and malnutrition (rarely). AÂ case report highlighting GMT as " starvation marrow" along with review of literature is being presented. (Med J Indones 2002; 11: 104-5)Keywords : malnutrition, bone marrow, gelatinous transformation